Proceedings of the 1st International Conference on Inter-Professional Health Collaboration (ICIHC 2018) 2019
DOI: 10.2991/icihc-18.2019.17
|View full text |Cite
|
Sign up to set email alerts
|

The Maternal Mobile Message Program Can Increase Knowledge And Attitude To Antenatal Care In Pregnant Women In Seluma District

Abstract: The 2012 Indonesian Demographic Survey shows that the Maternal Mortality Rate is still high; this is also the case in Seluma District in 2015. Education disparities and regions are obstacles to access and quality of services received, so information technology is needed to facilitate the delivery of information to healthy individuals who do not regularly contact health services through the use of mobile phones. This study aims to determine the effect of Maternal Mobile Message (M3) on knowledge to antenatal ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…Furthermore, text messages or Smartphone apps are very efficient in providing the required pregnancy care information to reduce health financing, increase understanding, insight, and information needs during pregnancy care. 1 Based on our study results, it can be concluded that pregnant women who participate in the online pregnancy class can understand the importance of pregnancy examinations and care. Pregnancy class is an approach that can be used to learn about pregnancy health and increase mothers' knowledge and skills about pregnancy examination and maintenance.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Furthermore, text messages or Smartphone apps are very efficient in providing the required pregnancy care information to reduce health financing, increase understanding, insight, and information needs during pregnancy care. 1 Based on our study results, it can be concluded that pregnant women who participate in the online pregnancy class can understand the importance of pregnancy examinations and care. Pregnancy class is an approach that can be used to learn about pregnancy health and increase mothers' knowledge and skills about pregnancy examination and maintenance.…”
Section: Discussionmentioning
confidence: 69%
“…MMR is also used to monitor mortality during pregnancy, associated with health status, education, and services during pregnancy and childbirth. 1 Therefore, MMR's sensitivity and its association with health services improvement indicate the success of the health sector development and still represents a significant concern of both central and local governments. 2 Pregnancy is a process that begins with conception and ends with labor.…”
Section: Introductionmentioning
confidence: 99%